Functional Outcomes and Complications After Oncologic Reconstruction of the Proximal Humerus. Issue 11 (1st June 2018) - Nota, Sjoerd; Teunis, Teun; Kortlever, Joost; Ferrone, Marco; Ready, John; Gebhardt, Mark; Raskin, Kevin; Hornicek, Francis; Schwab, Joseph; Lozano Calderon, Santiago
Abstract : Background: No consensus exists on the best method of articular reconstruction in patients who require proximal humerus resection for the management of primary bone sarcomas, soft-tissue sarcomas extending into the bone, benign and locally aggressive primary bone tumors, and metastatic disease. Methods: We identified patients from two institutions who underwent wide resection of the proximal humerus along with oncologic reconstruction using osteoarticular allografts (OAs), endoprostheses, or allograft-prosthesis composites. We prospectively collected functional outcomes and retrospectively assessed complications and implant survival. Results: A total of 150 patients were included in this study. The average Disabilities of the Arm, Shoulder and Hand questionnaire score was 26 for 25 patients, of which we gathered their functional data, with no differences in physical function among the three constructional methods according to the Disabilities of the Arm, Shoulder and Hand questionnaire, upper extremity Toronto Extremity Salvage Score, upper extremity Musculoskeletal Tumor Society, and Patient-Reported Outcomes Measurement Information System scores. Overall, the survival rate of the prosthesis was >50%. A trend was noted for a higher risk of failure in the OA group secondary to the allograft fracture. Discussion: All three articular oncologic shoulder reconstructions were comparable in terms of function. This large series confirms a higher fracture rate in OAs, which explains the observed higher revision rate and apparent lower survival rate in this subgroup.